Massive adrenal vein aneurysm mimicking an adrenal tumor in a patient with hemophilia A: a case report and review of the literature - Richard Sleightholm; Steven Wahlmeier; Jeffrey S. Carson; Andjela Drincic; Audrey Lazenby; Jason M. Foster (Journal of Medical Case Reports, 2016)
Abstract Background Visceral venous aneurysms are exceedingly rare, and until now, there have been no reports of this phenomenon in the adrenal vasculature. This report details the first adrenal venous aneurysm reported in the literature. The aneurysm presented as an 18-cm mass that was initially suspected to be a hematoma or tumor on the basis of the complex medical history of the patient, which included hemophilia A and testicular cancer. After surgical excision, pathologic examination confirmed this mass to be a 15.9-cm adrenal vein aneurysm, the largest aneurysm of any type or location recorded in the medical literature. Case presentation A 58-year-old caucasian male with hemophilia A presented to the emergency room of another institution with abdominal pain, blood in the stool, and a history of diverticulosis and symptomatic hemorrhoids. A large, left-sided adrenal mass was detected by computed tomography, and because of the patient’s hemophilia A and imaging consistent with a hemorrhagic mass, a hematoma was initially suspected. The patient was transferred to our institution, monitored for further bleeding with a stable hospital course, and discharged from the hospital under close monitoring. After 7–8 weeks with no change in the size of the mass, concerns grew regarding increasing symptoms of both satiety and mass effects from the large anomaly, as well as about the patient’s complicated medical history, which also included cancer. Surgical excision was recommended because of the concerns about increasing symptoms and the possibility of a malignancy. Correction and maintenance of factor VIII levels were incorporated pre-, intra-, and postoperatively, and en bloc surgical resection was performed to minimize bleeding and provide oncologic extirpation of the mass. A bowling ball-sized mass was removed, and careful pathologic examination revealed the mass to be a venous adrenal aneurysm. After a brief hospital stay, the patient made a full recovery. Extensive review of the literature revealed 11 reports of adrenal artery aneurysms but no reported case of an adrenal aneurysm arising from the venous system. Conclusions Several case reports suggest a correlation between hemophilia and aneurysms. In patients with inherited clotting disorders such as hemophilia A, aneurysms may present in atypical fashions and should be carefully ruled out.